To solve the equation (x - 1)/2 - 4 = 0 using quadratic formulas, we can first simplify the equation:
(x - 1)/2 - 4 = 0
Multiply both sides of the equation by 2 to eliminate the denominator:
2[(x - 1)/2 - 4] = 2(0)
(x - 1) - 8 = 0
x - 1 - 8 = 0
x - 9 = 0
Now, the equation is in the form ax^2 + bx + c = 0, where a = 1, b = -9, and c = 0.
To find the values of x that satisfy the equation, we can use the quadratic formula:
x = (-b ± √(b^2 - 4ac)) / (2a)
Plugging in the values, we have:
x = (-(-9) ± √((-9)^2 - 4(1)(0))) / (2(1))
x = (9 ± √(81 - 0)) / 2
x = (9 ± √81) / 2
x = (9 ± 9) / 2
x = (9 + 9) / 2 or x = (9 - 9) / 2
x = 18 / 2 or x = 0 / 2
x = 9 or x = 0
So, the solutions to the equation (x - 1)/2 - 4 = 0 are x = 9 and x = 0.
Using quadratic formulas to solve each equation.
(x - 1)/2 - 4 = 0
1 answer